Oikeuskirjallisuuden roolista perustuslakivaliokunnan ratkaisutoiminnassa - Koskentausta, Lauri (Lakimies, 2022)
Role of legal literature in the decision-making of the Constitutional Law Committee of the Parliament of Finland The article examines the significance of legal literature in the decision-making of the Constitutional Law Committee of the Parliament of Finland. Legal literature has traditionally played a minor role in Finnish judicial practice, but it has nonetheless been accepted as a source of law that can be cited. That said, there is no legal obligation to cite legal literature. As for the Constitutional Law Committee, it has been stated that the Committee mainly relies on its decision-making on the travaux préparatoires of the Constitution and on its own previous practice. Legal literature has been considered to have significance mainly in the development of general doctrines and formation of concepts that take place in the Committee. The author notes that the Constitutional Law Committee has referred to legal literature in its reports and statements 20 times since the present Constitution entered into force in 2000, while the experts heard by the Committee have referred to legal literature in their statements about 100 times since 2015. The references in the Committee’s opinions have mainly related to the interpretation of a few sections of the Constitution. In contrast, the experts heard by the committee have referred to legal literature in very different situations and for different reasons. The author states that the Committee and the experts seem to consider that legal literature is a permitted source of law, at least to some extent.